The correlation between demographic, health characteristic and medical tourism perception among Chinese tourists in Bangkok, Thailand - Liu, Zhuang; Hounnaklang, Nuchanad (Journal of Health Research, 2018)
Purpose - Recently, medical tourism is quietly rising all over the world. Chinese tourists have signed up through travel agencies to participate in overseas medical examinations. The purpose of this study was to investigate the correlation between demographic, health characteristic and Medical Tourism Perception (MTP) among Chinese tourists. Design/methodology/approach - The research was a cross-sectional study. 481 Chinese tourists were recruited to participate in the study in Bangkok in 2018. The 56-item Questionnaire was used as an instrument for measuring Chinese tourists’ perceptions toward medical tourism in Bangkok, Thailand. Data was analyzed by using descriptive statistics and correlation. Findings - Among variables, gender, age, marital status, occupation, illness history, medical tourism history and insurance, did not have a correlation with MTP. Education had low negative correlation (p-value<0.05) with MTP. As the educational level of Chinese tourists has increased, their choice of Thailand as a destination for medical tourism has declined. Originality/value - The research can be used as a guideline for tourism stakeholders and medical tourism related organizations in order to establish medical tourism policy more productively and efficiently.